Meningkatkan Keterampilan Menyimak melalui Dongeng Golek Daun Singkong Pada Siswa Sekolah Dasar - Nazmi, Lailatun; Lyesmaya, Dyah; Nurmeta, Irna Khaleda (Jayapangus Press, 2025)
This study was prepared with the aim of improving listening skills using cassava leaf golek media played by reading fairy tales to class IV.2 SDN Pakujajar CBM Kota Sukabumi students in the 2024/2025 school year. This study used a type of classroom action research (CAR) with a research design using the Kemmis and MC Taggart model. This research was carried out with two cycles, each cycle starting with research planning, action, observation or observation and reflection. The instruments used for data collection are teacher and student activity observation sheets as well as tests using LKPD. The results of the study in cycle I where 45% of students had good listening skills with an average score of 60.3 and increased in cycle II with 84% already having very good listening skills with an average score of 87.5. In addition, the results of observations of teacher and student activities in cycle I were 53.2 for students and 65.5 for teachers and increased in cycle II which was 86.3 for students and 89.4 for teachers. This cassava leaf golek media can attract students in learning so that students can do listening activities well.